At‐vessel mortality of skates (Rajidae) taken in coastal fisheries and evidence of longer‐term survival. Issue 6 (19th April 2018) - Ellis, J. R.; Burt, G. J.; Grilli, G.; McCully Phillips, S. R.; Catchpole, T. L.; Maxwell, D. L.
Abstract : Data on the vigour and at‐vessel mortality (AVM) of 6798 skates (comprising Raja clavata n =  6295; R. brachyura n =  208; R. undulata n =  185, R. montagui n =  98 and R. microocellata n =  12) captured by commercial fishing vessels in the inshore waters of the southern North Sea and English Channel were recorded. AVM in longline fisheries averaged 0·44% across five vessels (0–1·47%), although skates were usually unhooked manually and did not usually pass through a bait‐stripper. AVM in otter trawls averaged 0·76% (0–2·35%), from four vessels fishing with tow durations of <1·5 h (southern North Sea) or 1–4 h (English Channel). No AVM was noted for skates taken as a by‐catch in drift trammel nets (soak times <4 h). Anchored tangle nets resulted in an overall AVM of 2·0–2·7%, but increased from 1·47% (13–28 h soak time) to 6·16% (42–53 h soak time). There were significant differences in the vigour of skates between gears, with R. clavata caught by longline and tangle nets in better condition than those captured by otter trawl or drift trammel net. Similarly, R. undulata caught by tangle net were in better condition than those caught by otter trawl. The vigour of R. undulata was also found to be higher than other skate species for both trawl and tangle net. In total, 5283 skates were tagged with Petersen discs and released, with recapture rates for the various combinations of vessel and gear ranging up to 24·8% for R. clavata . Whilst confirming a degree of post‐release survival, quantitative estimates of post‐release mortality for skates remain unknown.